Whistleblowing and Islamic Ethics in Preventing Fraud: Pelaporan Pelanggaran dan Etika Islam dalam Mencegah Penipuan - Via, Varadila Isnada Alif; Abidin, Fityan Izza Noor (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Fraud poses a significant threat to companies, causing financial losses and reputational damage, with preventive measures being more effective than repressive actions. Specific Background: In organizational contexts, the integration of whistleblowing mechanisms and Islamic ethics offers a framework for mitigating fraudulent behavior, yet empirical studies examining their combined role remain limited. Knowledge Gap: Existing research often addresses whistleblowing or ethical principles separately, lacking comprehensive insights into their joint contribution to fraud prevention within regional public companies. Aims: This study investigates the role of whistleblowing and Islamic ethics in preventing fraud among employees of Delta Tirta Sidoarjo Regional Public Company (PERUMDA). Methods: A descriptive qualitative approach was applied, utilizing interviews, observations, and documentation, with data validity ensured through triangulation. Results: Findings indicate that whistleblowing and Islamic ethics effectively prevent fraud by aligning with the Guidelines for Reporting Violations set by the National Committee on Governance Policy. Novelty: The study highlights the combined role of ethical and procedural mechanisms in fraud prevention, emphasizing the need for strengthened legal protection of whistleblowers. Implications: This research provides practical guidance for organizations seeking sustainable strategies to minimize fraud and enhance ethical compliance. Highlights: Combines ethical values and procedural mechanisms to prevent fraud. Highlights legal protection as critical for sustainable whistleblowing. Provides practical guidance for corporate fraud mitigation. Keywords: Whistleblowing, Islamic Ethics, Fraud Prevention, Organizational Governance, Employee Compliance